Modified Buried Vertical Mattress Suture Versus Buried Intradermal Suture: A Prospective Split-Scar Study. Issue 3 (11th March 2021) - Liu, Zonghui; Tang, Zhishui; Hao, Xiaoyan; Liu, Xiangyu; He, Lin; Yu, Xueyuan; Wang, Rui; He, Youcheng; Guo, Yuan; Shu, Maoguo
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: The modified buried vertical mattress suture (MBVMS) is believed to provide excellent outcomes by relieving the tension on wound edges. However, clinical data on the topic remain sparse and inadequate. OBJECTIVE: To compare the cosmetic results of the MBVMS and the buried intradermal suture (BIS) in chest wounds using a split-scar model. MATERIALS AND METHODS: Twenty patients participated in the study. One randomly selected half of each chest wound was closed with the MBVMS; the other half was closed with the BIS. Immediately, postoperatively, the maximum degree of wound eversion was obtained. After 3 months, the wound complication rates were recorded, and the aesthetic appearance of each scar was evaluated by the Patient and Observer Scar Assessment Scale (POSAS), the Vancouver Scar Scale (VSS), the visual analog scale (VAS), and scar width. RESULTS: The MBVMS yielded a greater mean postoperative eversion height and width ( p < .05); lower POSAS, VSS, and VAS scores ( p < .05); and a narrower scar width ( p < .05) than did the BIS. CONCLUSION: Compared with the BIS, the MBVMS provided significantly increased wound eversion immediately, postoperatively, and improved aesthetic outcomes at the end of the 3-month follow-up period.